Atypical Rett syndrome form – case study = Nietypowa postać zespółu Retta – opis przypadku - Kochański, Bartosz; Plaskiewicz, Anna; Kałużny, Krystian; Pawilicka, Aleksandra; Smuczyński, Wojciech; Hagner-Derengowska, Magdalena; Zukow, Walery; Hagner, Wojciech (Journal of Education, Health and Sport, 2015)
Kochański Bartosz, Plaskiewicz Anna, Kałużny Krystian, Pawlicka Aleksandra, Smuczyński Wojciech, Hagner‑Derengowska Magdalena, Zukow Walery, Hagner Wojciech. Atypical Rett syndrome form – case study = Nietypowa postać zespółu Retta – opis przypadku. Journal of Education, Health and Sport. 2015;5(2):173-178. ISSN 2391-8306. DOI: 10.5281/zenodo.15846 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A173-178 https://pbn.nauka.gov.pl/works/543114 http://dx.doi.org/10.5281/zenodo.15846 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.02.2015. ATYPICAL RETT SYNDROME FORM – CASE STUDY NIETYPOWA POSTAĆ ZESPÓŁU RETTA – OPIS PRZYPADKU Bartosz Kochański1, Anna Plaskiewicz1, Krystian Kałużny1, Aleksandra Pawlicka2, Wojciech Smuczyński2, Magdalena Hagner-Derengowska3, Walery Zukow4, Wojciech Hagner1 1Katedra i Klinika Rehabilitacji, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu, Polska 2Klinika Neurochirurgii, Neurotraumatologii i Neurochirurgii Dziecięcej, Wydział Lekarski, Uniwersytet Mikołaja Kopernika w Toruniu, Polska 3Katedra Neuropsychologii Klinicznej, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu, Polska 4Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Polska Summary Rett syndrome is a rare, progressive neurological disorder that affects mostly female patients. It is a syndrome of pervasive developmental disorders of the neural, skeletal and gastrointestinal systems. According to the statistics Rett syndrome occurs in approximately 1 : 10 000 – 15 000 live births. Besides the classical form of the syndrome, there exist an atypical variation and the clinically distinct form with preserved speech. The authors present a case of a patient suffering from atypical Rett syndrome variant, with no MECP2 gene mutation. Key words: Rett syndrome, MECP2, atypical Rett Syndrome form. Streszczenie Zespół Retta jest rzadkim, postępującym schorzeniem neurologicznym występującym głównie u dziewczynek. Jest to zespół całościowych zaburzeń rozwoju współistniejących w obrębie układu nerwowego, szkieletowego oraz żołądkowo-jelitowego. Według danych statystycznych częstość występowania zespołu Retta szacowana jest na 1: 10 000 – 15 000 urodzeń. W zespole Retta można wyróżnić klasyczną postać, nietypową postać oraz postać odmienną klinicznie z zachowaną mową. Autorzy przedstawiają opis przypadku pacjentki z nietypową postacią zespołu Retta, u której nie występuje mutacja genu MECP2. Słowa kluczowe: zespół Retta, MECP2, nietypowa postać zespołu Retta.